FLOCCULANTS OPTIMIZATION IN HARVESTING FRESHWATER MICROALGAE Haematococcus pluvialis - Dina Soes Putri; Desy Ambar Sari; Lulu Diani Zuhdia (Jurnal Kimia Riset, 2020)
Microalgae-based researches are one of the interesting topics to date due to its wide applications for commercial industries. One of the vital issues that remain in the production of large-scale microalgae is the harvesting process of microalgae culture. There are several techniques that can be used in harvesting microalgae and each algae will be showing a different result. In this research, the microalgae Haematococcus pluvialis were harvested using flocculation-filtration method. Alum in different dosages, range from 0.25-2 g/L, was used as flocculants and the mixing duration was investigated to seek out the best harvesting efficiency. Based on the research, it can be concluded that the optimum flocculation process was alum addition of 1 g/L culture that continuously stirring for 5 minutes long. In which the flocculation efficiency reaches 94.5%.